Knowledge regarding infection control procedures among dental students at the International University for Science and Technology, Syria - Dannan, Aous Fozi; Al-Labban, Sham (Journal of medical and pharmaceutical sciences, 2022)
The purpose of this study was to evaluate the level of awareness and knowledge of infection control procedures among dental students at the International University for Science and Technology, Syria. The study comprised of 121 subjects of 3rd ,4th, and 5th year dental students. A questionnaire was developed which included 10 questions related to dental instruments’ storage, handling the dental chair, Personal Protective Equipment’s, and knowledge about the sterilization technique. This questionnaire was distributed among the dental students to be directly answered. The collected data were demonstrated after descriptive statistics. More efforts are still needed to increase the level of awareness to infection control procedures among students due to the rising risk of infection transmission at dental clinics.